2017
DOI: 10.1107/s2056989017005448
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure of (S)-sec-butylammonium L-tartrate monohydrate

Abstract: The title hydrated mol­ecular salt was prepared by deprotonation of enanti­opure l-tartaric acid with racemic sec-butyl­amine in water. Only one enanti­omer was observed crystallographically, resulting from the combination of (S)-sec-butyl­amine with l-tartaric acid.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…However, preliminary tests had shown that when lyophilizing acidic solutions of 2-aminobutane and IPA in water, up to 25% of the initially added mass were lost, presumably due to the same apparent sublimation that is also observed for ammonium chloride. Precipitation of 2-aminobutane from the reaction mixture using tartaric acid also proved to be ineffective (data not shown).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, preliminary tests had shown that when lyophilizing acidic solutions of 2-aminobutane and IPA in water, up to 25% of the initially added mass were lost, presumably due to the same apparent sublimation that is also observed for ammonium chloride. Precipitation of 2-aminobutane from the reaction mixture using tartaric acid also proved to be ineffective (data not shown).…”
Section: Resultsmentioning
confidence: 99%
“…The similar size of the R-groups (ethyl vs methyl) poses a challenge in achieving high enantioselectivity. Racemic 2-aminobutane may be separated into its enantiomers by classical resolution using tartaric acid . A recently reported asymmetric synthesis employing a chiral ruthenium catalyst only achieved 22% ee, among the lowest enantioselectivities for the substrates tried by the authors .…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation